Phosphine-free manganese(II)-catalyst enables acceptorless dehydrogenative coupling of alcohols with indoles - Yadav, Vinita; Balaraman, Ekambaram; Mhaske, Santosh B. (Advanced Synthesis & Catalysis, 2021)
Herein, an air-stable, molecularly defined NNN-Mn(II) pincer complex catalyzed acceptorless dehydrogenative coupling of alcohols with indoles is reported. A wide variety of symmetrical and unsymmetrical bis(indolyl)methane derivatives as well as some structurally important products such as Vibrindole A, Turbomycin B alkaloid, Antileukemic, and Anticancer agents were synthesized. Mechanistic studies illustrate the importance of the NH moiety in the complex and the crucial role of metal-ligand cooperation during catalysis.
Keywords: acceptorless dehydrogenation; Alcohol; Indole; manganese; phosphine-free